PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2021 - Elih Ermawati; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this research is to test and prove the influence of fundamental factors on financial distress in companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the 2016-2021 period. The population of this study uses all companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the 2016-2021 period, where 80 companies are the study population. The sampling technique in this study used a purposive sampling technique, where samples were obtained from populations that met the specified criteria. The results of determining the criteria using purposive sampling technique obtained 15 companies. As for the data analysis techniques used in this study include descriptive statistical analysis (mean, maximum, minimum, range, standard deviation), classic assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test) and hypothesis testing (statistical test t). The results of this study indicate that return on equity partially has no effect on the financial distress index, debt to equity ratio partially has no effect on the financial distress index, while the quick ratio partially has an influence on the financial distress index.